The Effectiveness of Bilingual Learning for Students in the Era of Globalization - Tiarnita Maria Sarjani Br. Siregar; Rini Luthfiani; Alifia Rahmadita; Rayna Br. Saragih; Mahfira Artia Rahma (Peneliti.net, 2026)
Bilingual learning is one of the strategies of higher education in facing the demands of globalization, particularly in improving foreign language proficiency and preparing students to compete internationally. This study aims to assess the effectiveness of implementing bilingual learning in higher education and identify factors influencing its success. The research method used is a literature review by analyzing various relevant scientific articles published within the last five years (2020–2025). Data sources were obtained through searches in academic databases such as Google Scholar, Scopus, SINTA, and Garuda using keywords related to bilingual learning and higher education. The study results indicate that bilingual learning generally has a positive impact on improving students' language skills, broadening their academic horizons, and preparing them for the global workplace. However, its effectiveness is greatly influenced by lecturer competence, student preparedness, the availability of teaching materials, and a supportive academic environment. The main obstacles identified include differences in language proficiency levels, limited English proficiency among teachers, and low motivation among some students. Therefore, implementing bilingual learning requires a well-planned strategy, ongoing lecturer training, and the development of institutional policies that support optimal program implementation.